Blood Transfusion Therapy in Patients with Autoimmune Hemolytic Anemia - Irma, Fani Ade (Buletin Farmatera, 2022)
Management therapy of autoimmune hemolytic anemia (AIHA) with severe clinical symptoms requires supportive therapy such as blood components transfusion to improve hemodynamic conditions. This literature study aims to explain the role of blood transfusion therapy in AIHA cases. The method used is through searching articles in national and international journals published in the last 10 years that discuss transfusion in AIHA cases using the Google Scholar application. From the search results, it can be concluded that blood transfusion is a supportive therapy in cases of AIHA with symptoms of severe hypoxemia that interfere with hemodynamics and work function of body organ systems and findings of Hb levels 7 mg/dL with the selection of blood components in the form of packed red cells (PRC), washed packed red cells (WPRC) and Leucoreduction (LR).